Investigating the compressive behavior of zeolite-based porous mechanical metamaterials - Dosung Lee; JunHo Song; Kyoungmin Min; Namjung Kim (Materials & Design)
Modern additive manufacturing technology leverages the robustness and efficiency of natural systems, offering precision and customizability in design. Despite advancements in mechanical metamaterials, structures that combine superior mechanical properties with material efficiency are required. This study proposes zeolite-based porous mechanical metamaterials and investigates their compressive behaviors. From a theoretical pool of approximately 590,000 units, 21 zeolite unit cells were selected based on isotropy and manufacturability. Accordingly, supercells were generated to mitigate boundary effects. Macroscopic structures were fabricated via stereolithography from supercell electron densities using hyperelastic materials. Mechanical properties were assessed via numerical simulations and compression tests, verified with digital image correlation. The selected structures were categorized into four groups based on their stress–strain responses: nonlinear, linear, bilinear, and collapsed. Although geometrical variations in the zeolite structures significantly influenced their stress–strain behavior, these variations exerted a lesser impact on energy absorption at large deformations. Notably, the nonlinear group exhibited a higher average Young’s modulus (0.403 MPa), compressive stress (0.780 MPa), and energy absorption (139,498 J/m3) than other groups, while the linear group exhibited an average Young’s modulus per volume fraction 9.52 % higher than other groups. These findings indicate that zeolite-based metamaterials provide design insights into optimization for diverse applications.